Interim Results of Intercropping of Miscellaneous Tree Species with Main Crop of Taungya Plantations to Increase the Productivity - Tiwari, K. M. (Indian Forester, 1970)
In order to guard against some of the harmful effects of monoculture in plantation practice, an experiment was laid out to introduce miscellaneous species of multipurpose value-particularly species known to improve the soil humus and which are useful as fuel and fodder-in the interspaces of Sal taungya lines when cultivators have left the area. It has been found that it is possible to raise economically species like Albi a Procera, Bauhinia variegata, Cassia fistula and Ougeinia oojeinensis without any adverse effect on the main crop. An additional yield of approximately 1 tonne/ha/year was obtained on a 4 year rotation of miscellaneous species. Other beneficial effects of miscellaneous species are also discussed.